Compact Dual-band Parallel Coupled T-shaped SIR Filter for WLAN Applications - Emad S. Ahmaed (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2017)
In this article, a new compact dual-band bandpass filter was introduced. The filter utilized two operating bands centered at 2.45 GHz and 5 GHz widely used for wireless local area network applications. The filter consists of T-shaped sections of step impedance resonator. The structure is an even symmetrical around electrical or magnetic wall, so the operation mechanism of the filter can be analyzed by an even- and odd-mode transmission line theory. The resonator structure is parallel coupled to a pair of 50 Ω input/output ports. Proper feeding and coupling structures can realize at least two transmission zeros around each of the operating band. To enhance the spurs rejection in the out of the band response of the filter, additive transmission zero at 10 GHz was created by adding stub of quarter guided wavelength at a selected distant from the output port edge. The filter is designed and optimized using the full wave Electromagnetic simulator. The center frequency of the designed bands can be easily refined by the filter dimensions. The overall dimension of the filter is (where  is the guided wavelength at the frequency of 2.45 GHz) corresponding to 14.3 mm x 22 mm.